IMMUNOMODULATORY EFFECT TEST FROM MORINGA LEAF EXTRACT (MORINGA OLEIFERA L.) WITH CARBON CLEARANCE METHOD IN MALE WHITE MICE - Dillasamola, Dwisari; Aldi, Yufri; Fakhri, Mutia; Diliarosta, Skunda; P, Biomechy Oktomalio; Noverial (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Moringa oleifera leaf has chemical compounds that have been utilized by the community to cure health problems. One of its activities is an immunomodulator. The aim of this study is to determine the immunomodulatory effect from M. oleifera leaf using a carbon clearance method to measure the activity of phagocytic cells in exterminating pathogens that enter the body then followed by calculating the total leukocyte cells. The parameters of this test are phagocytosis index and total leukocyte cells. Methods: Twenty white male mice were divided into four groups. Group I (vehicle control) was treated with sodium-carboxymethyl cellulose (NaCMC) 0.5%, Group II-IV were treated by M. oleifera leaf extract given to the mice for six consecutive days orally in doses of 10, 30, 100 mg/kg. On the seventh day, white male mice were given with intravenous carbon suspension through their tails. The value of phagocytosis index (PI > 1) indicated immunostimulant activity. The data were analyzed by using one-way analysis of variance and Duncan test. Results: The analysis of variance results showed that the groups treated with Moringa leaf extract are significantly different with the vehicle groups (NaCMC 0.5%) (p<0.05). Increased doses of Moringa leaf extract are effective to improve the immunomodulator effect. It was included that Moringa leaf extract had the immunomodulatory capabilities as an immunostimulant. Conclusion: Immunomodulatory effect test of M. oleifera Lam. Based on the result of the research about immunomodulatory effect test from Moringa leaf extract (Moringa Oleifera L.) with carbon clearance method in male white mice, it can be concluded that Moringa leaf extract (Moringa Oleifera L.) has effect as an Immunomodulator.